Daratumumab monotherapy in a patient with kappa light chain multiple myeloma and decompensated cirrhosis: a case report - Yang, Xiying; Liu, Zhiqian; Zhou, Yangyan; Zhang, Hua; Yang, Min; Wang, Hong (Frontiers in Oncology, 2025)
BackgroundMultiple myeloma (MM) rarely presents as decompensated liver cirrhosis, posing a significant diagnostic challenge that can lead to misdiagnosis and delayed treatment. We report a case of kappa-light chain multiple myeloma (κ-LCMM) initially managed as end-stage liver disease to highlight the diagnostic pathway and a successful, organ-reversing therapeutic outcome.Case presentationWe report the case of a 67-year-old male who presented with decompensated liver cirrhosis and refractory ascites as the initial manifestation of multiple myeloma. Serum free light chain assay revealed a kappa level of 47,309.88 mg/L, and bone marrow biopsy confirmed kappa-light chain multiple myeloma with 60% plasma cell infiltration. A profound clinical response, including reversal of hepato-renal dysfunction, was observed following targeted monotherapy with daratumumab.ConclusionsThis case underscores the critical importance of including plasma cell dyscrasias in the differential diagnosis of unexplained cirrhosis, particularly when accompanied by decreased immunoglobulin levels. The serum free light chain assay is an essential tool for facilitating a timely diagnosis. Furthermore, our findings suggest that daratumumab monotherapy can be a safe and highly effective therapeutic strategy for achieving deep, durable responses and reversing severe organ damage in patients with multiple myeloma.